2018
DOI: 10.1088/1741-4326/aadca1
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of GENE on ASDEX Upgrade using perturbative thermal diffusivity measured with partial sawtooth heat pulses

Abstract: Perturbative thermal diffusivity is measured with partial sawtooth-generated heat pulses on ASDEX Upgrade for the first time, and these measurements are used to validate the first nonlinear ion-scale gyrokinetic simulation that agrees with experimentally measured perturbative diffusivity. Recent work on Alcator C-Mod [N.T. Howard et al., Phys. Plasmas 23, 056109 (2016)] and DIII-D [C. Holland et al., Nucl. Fusion 57, 066043 (2017)] has shown that ion-scale gyrokinetics cannot adequately describe certain plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This is supported by extensive verification and validation work, e.g. in [15][16][17][18][19][20][21][22] regarding heat transport, which is the main focus of this paper, but also regarding main particle, impurity and momentum transport (see e.g. [23][24][25][26][27][28]).…”
Section: Non-linear Gyrokinetic and Reduced Modelsmentioning
confidence: 74%
“…This is supported by extensive verification and validation work, e.g. in [15][16][17][18][19][20][21][22] regarding heat transport, which is the main focus of this paper, but also regarding main particle, impurity and momentum transport (see e.g. [23][24][25][26][27][28]).…”
Section: Non-linear Gyrokinetic and Reduced Modelsmentioning
confidence: 74%
“…This quantification was used to develop criteria with which one is able to determine whether or not multi-scale effects will be important in a plasma discharge, without performing nonlinear simulations. These criteria are based on properties of the linear growth rates of the plasmas, similar to some past work, which suggested that g g -k k high low might be one such criterion [13,16,19]. In this criterion, g -k high is the 5 To address a possible confusion, note that c Ricci is not a diffusivity (unlike c e pert ) and is unitless.…”
Section: Riccimentioning
confidence: 94%
“…The perturbative diffusivity therefore measures the extent to which a change in the electron temperature gradient changes the electron heat flux. This study uses the propagation of partial sawtooth generated heat pulses in order to measure the perturbative diffusivity [18,19]. In particular, the Extended-Time-to-Peak calculation method [42] is used on heat pulses generated by partial sawteeth, as these avoid complications associated with full sawteeth [43].…”
Section: Machines and Experimental Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both models predict a continuous spectrum of electron modes are unstable above k y ρ s = 1, which smoothly transition from a TEM mode at k y ρ s ∼ 1 to the ETG mode by k y ρ e ∼ 0.5-1 (k y ρ s ∼ 30-60). However, both models also predict that these electron modes have growth rates which are still sufficiently small that they are not expected to contribute significantly to transport, based on published criteria [53]. Because of the focus on ion thermal transport in this work, and computational expense of nonlinear multiscale simulations which would self-consistently include both ITG and ETG dynamics, these short-wavelength modes are not considered further in this paper.…”
Section: Comparisons Of Tglf and Cgyro Linear Growth Ratesmentioning
confidence: 99%